2009
DOI: 10.1093/scan/nsn048
|View full text |Cite
|
Sign up to set email alerts
|

The amygdala response to images with impact

Abstract: Effective photojournalism provokes an emotional reaction and leaves a lasting impression upon the viewer. Striking and memorable images are often said to possess 'impact'. Within cognitive neuroscience memorable emotional images evoke a greater amygdala response. Research to date has focused on arousal as a causative factor, while the contribution of appraisal dimensions relating to salience of an item, goal relevance, or impact are yet to be addressed. We explored how differences in ratings of impact influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
75
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(88 citation statements)
references
References 37 publications
13
75
0
Order By: Relevance
“…It is also possible that the lack of effect of ESUP on the ratings of negative stimuli reflected their higher arousal values relative to the positive stimuli (see Section 2), although this difference had no such effect in the REAP condition. Because social stimuli typically tend to be judged as more arousing than nonsocial stimuli (Ewbank et al, 2009), we could not totally match emotion intensity between positive and negative scenes in order to obtain similar valence values for the more crucial comparisons of social and nonsocial content. Thus, social and nonsocial images were well matched on arousal (and control) judgments, and showed similar changes in subjective ratings across the different ER conditions.…”
Section: Behavioral Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible that the lack of effect of ESUP on the ratings of negative stimuli reflected their higher arousal values relative to the positive stimuli (see Section 2), although this difference had no such effect in the REAP condition. Because social stimuli typically tend to be judged as more arousing than nonsocial stimuli (Ewbank et al, 2009), we could not totally match emotion intensity between positive and negative scenes in order to obtain similar valence values for the more crucial comparisons of social and nonsocial content. Thus, social and nonsocial images were well matched on arousal (and control) judgments, and showed similar changes in subjective ratings across the different ER conditions.…”
Section: Behavioral Resultsmentioning
confidence: 99%
“…The final distribution of pictures in these four categories as a function of emotional rating scores (PLN, INT, and CON) showed that NEG images had significantly lower pleasantness scores as compared to POS images [PLNNEG = 20.67 ± 6.02 and PLNPOS = 72.14 ± 10.19; F(1,59) = 3919.25, p < .001], but also higher intensity [INTNEG = 70.08 [ANOVA]). Note that the differences in intensity between negative and positive stimuli could not be avoided in order to match pairs of social and nonsocial scenes in both valence conditions, because social material is otherwise typically judged as much more intense than nonsocial material (Ewbank, Barnard, Croucher, Ramponi, & Calder, 2009). Finally, we also selected 40 neutral images from the IAPS database (20 including humans, 20 without humans) to be used in a baseline control condition (see below), with average valence ratings of 49.7 ± 1.7 (on the same scale of 1-100).…”
Section: Stimulimentioning
confidence: 99%
“…As the ventral striatum has been shown to encode the subjective value of rewards associated with a stimulus (Delgado, 2007), it should reflect differences in the valuation of the monetary rewards, which may drive more self-interested vs. altruistic decisions. Similar predictions may be made about the amygdala, which reflects the individual relevance or impact of a stimulus (Ewbank et al, 2009;Sander et al, 2003). (B) When participants are trying to overcome a habitual response during a GO/ NOGO task, neural activity to the NOGO stimuli reflects openness to change value.…”
Section: Introductionmentioning
confidence: 82%
“…It maintains information about the rewarding properties of action outcomes, so that actions associated with greater long-term reward value can be chosen more frequently . The amygdala, whose activity is tightly synchronized with striatal activity during reward processing (Popescu, Popa, & Pare, 2009), determines the relevance of a stimulus for the needs and goals of an organism (Sander, Grafman, & Zalla, 2003;Sergerie, Chochol, & Armony, 2008), and shows stronger responses to stimuli that are perceived as having a subjective "impact" on the individual (Ewbank, Barnard, Croucher, Ramponi, & Calder, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Based on [11] we know that it is actually relevant to consider one unique measure qualifying emotions, which is "impact" instead of the traditional arousal, and valence measures.…”
Section: Building a Relationshipmentioning
confidence: 99%